2014
DOI: 10.7314/apjcp.2014.15.21.9211
|View full text |Cite
|
Sign up to set email alerts
|

Role of CXCR7 and Effects on CXCL12 in SiHa Cells and Upregulation in Cervical Squamous Cell Carcinomas in Uighur Women

Abstract: CXCR7 is involved in tumor development and metastasis in multiple malignancies. However, the function and molecular mechanisms of action of CXCR7 in human cervical cancer are still unclear. In the present study a loss of-function approach was used to observe the effects of recombinant CXCR7 specific small interfering RNA pBSilence1.1 plasmids on biological behavior including proliferative activity and invasive potential, as indicated by MTT assays with the cervical cancer SiHa cell line in vitro. Reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Among 27 studies, three studies each evaluated colorectal carcinoma (or rectal cancer) 18 - 20 , hepatocellular carcinoma 21 - 23 , esophageal carcinoma (or esophageal squamous cell carcinoma) 13 , 24 , 25 , and thyroid carcinoma 26 - 28 . Two studies evaluated renal cell carcinoma 29 , 30 , pancreatic cancer 31 , 32 , cervical cancer (or cervical squamous cell carcinoma) 33 , 34 , nasopharyngeal carcinoma 35 , 36 , glioma or glioblastoma 37 , 38 and gastric cancer 39 , 40 . One study evaluated gallbladder cancer 14 , cutaneous squamous cell carcinoma 41 and chondrosarcoma 42 .…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Among 27 studies, three studies each evaluated colorectal carcinoma (or rectal cancer) 18 - 20 , hepatocellular carcinoma 21 - 23 , esophageal carcinoma (or esophageal squamous cell carcinoma) 13 , 24 , 25 , and thyroid carcinoma 26 - 28 . Two studies evaluated renal cell carcinoma 29 , 30 , pancreatic cancer 31 , 32 , cervical cancer (or cervical squamous cell carcinoma) 33 , 34 , nasopharyngeal carcinoma 35 , 36 , glioma or glioblastoma 37 , 38 and gastric cancer 39 , 40 . One study evaluated gallbladder cancer 14 , cutaneous squamous cell carcinoma 41 and chondrosarcoma 42 .…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Previously, it was reported that CXCR7 expression was higher in cervical cancer compared to CIN and normal cervical mucosa, particularly in those with an advanced stage of cancer and lymph node metastasis (10). However, the difference in CXCR7 protein expression among different stages of CIN has not been previously investigated and the ROC curve analysis has not been performed.…”
Section: Discussionmentioning
confidence: 97%
“…The present study utilized SiHa cervical carcinoma cell line, which was described as a squamous carcinoma cell line 22 and exhibited medium level of Twist1 expression among four cervical cell lines (data not shown). Previous study indicated that HIF-1α could bind directly to the hypoxia-response element (HRE) in Twist1 promoter to enhance Twist1 expression 9 .…”
Section: Discussionmentioning
confidence: 99%